Analysis of Some Public Debt Sustainability Alternative Indicators in Several Countries of the World in the Period 2001-2019: Array - Ailincă, Alina Georgeta (Acta Universitatis Danubius. Œconomica, 2021)
The COVID-19 health crisis has brought to light a series of shortcomings not only of a medical nature but also of the social, political, economic, cultural nature of all the countries of the world. In this context, indebtedness, especially public debt, has been the answer to many problems in all the countries of the world. The literature and international organizations are carefully and constantly concerned with improving indicators of public indebtedness assessment, including those for assessing debt sustainability. However, there are many areas still unexplored. Therefore, the article aims to highlight the link between public debt and a number of important macroeconomic indicators, including from the sphere of GDP (estimated according to the method of expenses), through the methods of advance coefficient and elasticity, in 11 countries of the world, in the pre COVID19 pandemic period 2001-2019.